“Escuchar para cambiar”: uma análise do processo de implementação da rede social Lazos durante a execução de programas internacionais de cooperação - Oliveira, Jozene Noal de (2022)
This dissertation comprehends the communinational strategies developed to the implementation of Lazos social media by the institutions involved in the international trilateral south-south cooperation project +Cotton in Paraguay. This project is a modality of international cooperation for development where countries share similar challenges and experiences. The reflections about this topic emerge from the importance of cotton production in Latin America and the need to inplement ICTs that promote the sustainable development of the cotton chain in peripheral regions of this territory. As a pilot project in Paraguay, the Lazos social media comes from the agreement between FAO and FATEC, linked to UFSM. The network is developed by the research group Communication for Development and took effect through the research project “Communication for Development: Latin America Lazos Project”, which considers the creation of technological platforms as a possibility to impact communities through communication for development (CpD). While we comprehend this network as a process, we question: how are the institutions involved with the Lazos social media, developing communication strategies for the implementation of this network in the course of the trilateral south-south international cooperation project +Cotton in Paraguay? Therefore, this dissertation is anchored in a qualitative methodology by performing a triangulation of techniques (GOLDENBERG, 2011; 2004; GÓMEZ, 2004; FIGARO, 2014; DUARTE, 2009). The theoretical basis triggers the theme of communication and organizational communication (PERUZZOLO, 2006; BALDISSERA, 2004; 2009), while inserts discussions about social capital and trust relationships (RECUERO, 2005; MATOS, 2007). We seek to highlight the construction of the idea of CpD (PNUD, 2011; SEN, 2000; PERUZZO, 1998; 2010) and to think about ICTs for social inclusion (VIERO; SILVEIRA, 2011; BIGNETTI, 2011; BAVA, 2004). In addition, we discuss international cooperation programs in Latin America (SATO, 2010; ABC, 2022), we present the international cooperation project +Cotton (MILANI, 2017; +ALGODÃO, 2022), we highlight some communication challenges of the cotton reality (SILVEIRA, 2019; CARVALHO, 2012; STROPASOLAS, 2006) and we discuss the importance of citizenship and democracy (PERUZZO, 2010; 2018; GUEDES; SILVA; SANTOS, 2017). The results point to several challenges faced by institutions in the establishment of communication strategies for the implementation of Lazos social media, precisely because of the bureaucratic confrontation. We also observed that proximity relationships are very important for strengthening connections between institutions and users, and the communication challenges linked to this process refer to the lack of communicational alignment from the perspective of CpD. We infer that the COVID-19 pandemic impacted this process, but it also demonstrated that this ICT is a space capable of maintaining socialization ties based on the consideration of a hybrid online and offline environment. In addition, we reflect that an alignment between all those involved in the implementation of the Lazos social network is fundamental, such as understanding its methodology and recognizing the communication strategies developed for the implementation, considering CpD as fundamental for maintaining the engagement and usability of the network.